Characteristics and Mechanism of Ammonia Nitrogen Removal by Heterotrophic Nitrification Bacterium Klebsiella pneumoniae LCU1 and Its Application in Wastewater Treatment - Meng Xu; Lifei Chen; Yizhen Xin; Xiangyu Wang; Zhuoya Wang; Xueqiang Meng; Wenyu Zhang; Haoyang Sun; Yifan Li; Wenzhe Zhang; Peng Wan; Bingshuai Geng; et al. (Microorganisms)
In this study, a novel strain exhibiting heterotrophic nitrification was screened; subsequently, the strain was identified as Klebsiella pneumoniae LCU1 using 16S rRNA gene sequencing. The aim of the study was to investigate the effects of external factors on the NH4+-N removal efficiency of strain LCU1 in order to elucidate the optimal conditions for NH4+-N removal by the strain and improve the removal efficiency. The findings indicated that the NH4+-N removal efficiency of the strain exceeded 80% under optimal conditions (sodium succinate carbon source, C/N ratio of 10, initial pH of 8.0, temperature of 30 °C, and speed of 180 rpm). The genome analysis of strain LCU1 showed that key genes involved in nitrogen metabolism, including narGHI, nirB, nxrAB, and nasAB, were successfully annotated; hao and amo were absent, but the nitrogen properties analysis determined that the strain had a heterotrophic nitrification ability. After 120 h, the NH4+-N removal efficiency of strain LCU1 was 34.5% at a high NH4+-N concentration of 2000 mg/L. More importantly, the NH4+-N removal efficiency of this strain was above 34.13% at higher Cu2+, Mn2+, and Zn2+ ion concentrations. Furthermore, strain LCU1 had the highest NH4+-N removal efficiency of 34.51% for unsterilised (LCU1-OC) aquaculture wastewater. This suggests that with intensive colonisation treatment, the strain has promising application potential in real wastewater treatment.